PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN (Studi Kasus Pada Restoran Fast Food KFC) - Indra Pramudiyanto (2013)
This study was conducted to determine whether the service quality affects customer satisfaction and loyalty in the fast food restaurant KFC. Respondents in the study were students active force UPN Veteran Jakarta from 2010 to 2012. Obtained a total sample of 100 students. The analysis technique used is the Path or path analysis and hypothesis testing using a significance to the 5% level of confidence. The results showed that the quality of service and customer satisfaction has a significant impact on customer loyalty, directly or indirectly.